Linnaea borealis L. var. borealis—In Vitro Cultures and Phytochemical Screening as a Dual Strategy for Its Ex Situ Conservation and a Source of Bioactive Compounds of the Rare Species - Barbara Thiem (MDPI AG, 2021)
Linnaea borealis L. (Twinflower)—a dwarf shrub in the Linnaeeae tribe of Caprifoliaceae family—is distributed across the Northern Hemisphere. By means of this study, a reliable protocol for efficient micropropagation of uniform L. borealis L. var. borealis plantlets has been provided for the first time; callus culture was also established. Different initial explants, types of cultures, media systems, and plant growth regulators in Murashige and Skoog (MS) media were tested. Agitated shoot cultures in the liquid media turned out to be the best system for the production of sustainable plant biomass. After stabilization of the callus lines, the highest growth index (c.a. 526%) was gained for callus maintained on MS enriched with picloram. TLC and UHPLC-HESI-HRMS analysis confirmed the presence of phenolic acids and flavonoids, and for the first time, the presence of iridoids and triterpenoid saponins in this species. Multiplication of L. borealis shoot culture provides renewable raw material, allowing for the assessment of the phytochemical profile, and, in the future, for the quantitative analyses and the studies of the biological activity of extracts, fractions, or isolated compounds. This is the first report on in vitro cultures of traditionally used L. borealis rare taxon and its biosynthetic potential.